The Influence of Workload and Work Motivation on Employee Performance at PT Tugu Reasuransi Indonesia - Ruth Elisabet Rosemary; Edison Siregar; Ganda T. Hutapea (Universitas Kristen Indonesia, 2023)
Workloads, work motivations and employee performances can influence each other. The scope of discussion in these studies is the employee of PT. Indonesian Reinsurance Monument. Purposes of these studies was to determining (1) the effects of workloads on the performances of PT. Tugu Reasuransi Indonesia, (2) influences of work motivations on performances of employee of PT. Tugu Reasuransi Indonesia, (3) the effects of workloads and work motivation simultaneously on performances of employees of PT. Indonesian Reinsurance Monument. Quantitative method in these studies used SPSS version 25. Population of these studies was all employee of PT. Tugu Reasuransi Indonesia, which has 110 Employees use saturate sample techniques, so that data processed is 86 people. Results of these studies are as follow: (1) effects of workloads on performances of PT. The Indonesian Reinsurance Monument obtained tcount (8.582) > ttable (1.988) with a significant levels of 0.00 <0.05. From these result stated that Ho was reject (Ha accept). That show that workload affect the performances of employee of PT. Tugu Reasuransi Indonesia, (2) influence of the work motivations on performances of employee of PT. The Indonesian Reinsurance Monument obtained tcount (5.743) > ttable (1.988) with a significant level of 0.00 <0.05. From these results it can be conclud that Ho is reject (Ha is accept). This shows thats work motivation affect the performances of employee of PT. Indonesian Reinsurance Monument. (3) effect of workloads and the work motivation simultaneously on performances of employee of PT. The Indonesian Reinsurance Monument obtained fcount (36.654) > ftable (3.11) with a significant level of 0.00 <0.05. From these result stated that Ho was reject (Ha accept). That indicates are workload and the work motivation simultaneously affect performances of employee of PT. Indonesian Reassurance Monument. Keywords: workload, work motivation, and employee performance